THE INFLUENCE OF ENGLISH LANGUAGE PROFICIENCY ON STUDENTS’ CAREER PROSPECTS - Toshmanova Sevinch Shodiyor qizi; Hasanova Sevinch Hotam qizi; Miyliyeva Xilola Sayfidinovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: In today’s increasingly interconnected world, English functions as the dominant language of global communication, higher education, research, and commerce. With the rapid growth of globalization, the need for professionals who can communicate effectively in English continues to expand. This paper analyzes the role of English language proficiency in shaping students’ career prospects, employability, professional growth, earning potential, and access to international education. The findings emphasize that strong English skills improve students’ competitiveness in the job market and prepare them for success in a global environment.